2019
DOI: 10.1093/rheumatology/key256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of new JAK inhibitors under development. Just more of the same?

Abstract: Janus kinase inhibition is promising in the treatment of RA, with already two oral drugs marketed. New compounds are under investigation that are more selective for Janus kinase 1 or Janus kinase 3. Phase II results for filgotinib, upadacitinib, peficitinib and decernotinib are reviewed showing almost consistently a fast dose-dependent clinical improvement similar to already approved drugs tofacitinib and baricitinib. I will reflect on the most frequently reported dose-dependent adverse events and laboratory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…A recent study has indicated that the new pathogenesis of hyperuricemia is mainly intestinal microbiota (Pascart & Lioté, 2019), but the specific pathogenesis of gut microbiota is unclear. Some studies have reported altered gut microbiome in gout patients (Shao et al, 2017), with gut bacteria expressing the gene of allantoinase significantly reduced (Crane, 2013), suggesting that altered gut microbiota may associate with gout, and therefore, may help distinguish gout patients from healthy patients and serve as new targets for disease treatment (Guo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has indicated that the new pathogenesis of hyperuricemia is mainly intestinal microbiota (Pascart & Lioté, 2019), but the specific pathogenesis of gut microbiota is unclear. Some studies have reported altered gut microbiome in gout patients (Shao et al, 2017), with gut bacteria expressing the gene of allantoinase significantly reduced (Crane, 2013), suggesting that altered gut microbiota may associate with gout, and therefore, may help distinguish gout patients from healthy patients and serve as new targets for disease treatment (Guo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Baricitinib was recently approved in Europe for the treatment of RA following the completion of a large phase III clinical trial programme in which it was administered in a once daily dosing regimen [17–20]. A number of other investigational oral jakinibs with varying selectivity for the four JAK enzymes have been evaluated in phase II trials in patients with RA and these studies will be discussed in the article by Dr Westhovens [21].…”
Section: Introductionmentioning
confidence: 99%
“…Variances in the clinical performance of both JAK inhibitors have been observed [ 22 ]. However, the reason for these differences are unknown given that they both TKIs target Janus Kinases resulting in a reduced STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%